Management of partnerships with Civil Society Organizations (CSO) post-regulatory framework (MROSC): Effectiveness of law 13.019/2014 in Campo Belo – MG (Brazil) (Desenvolvimento em Questão, 2026)
This article analyzes the effects of Law No. 13.019/2014 — the Legal Framework for Civil Society Organizations (MROSC) — on partnerships between local government and welfare organizations in Campo Belo–MG. It aims to assess the effectiveness of MROSC implementation at the municipal level, considering criteria such as legality, legitimacy, institutional alignment, and public value creation. The methodology combines qualitative and quantitative approaches, including document analysis, questionnaires with CSO representatives, and semi-structured interviews with public managers. The results indicate progress in the formalization of partnerships and attention to legal requirements and social control. However, challenges persist, such as the frequent use of exemption from public calls and weak monitoring and evaluation mechanisms. Based on Cabral’s (2015) seven categories of effectiveness, the study identifies advances in institutional alignment and shared public values but also highlights gaps in democratic deliberation and political sustainability. The findings reinforce the need for institutional strengthening, technical training for both public managers and CSO leaders, and closer articulation with government planning instruments. The study concludes that while MROSC has enhanced regulation and transparency, its effectiveness relies on participatory practices and continuous evaluation mechanisms.
Keywords: Civil Society Organizations Legal Framework; Policy Effectiveness; State–Civil Society Partnerships; Local Government Management; Civil Society Organizations (CSOs)